Geotechnics in the promotion of dimension stone (Journal of Nepal Geological Society, 2000)
Changes in the supply and use of dimension stone have extensively modified the approach of the engineering geologist to stone technology. Traditional expertise requirements have moved from exploration, extraction, and processing to quality control and application.Reasons for this are the globalisation of dimension stone supplies from new and unknown sources; deterioration of environmental conditions; cost saving in using thin stone tiles or slabs as veneer; at times hazardous; incorrect cladding applications, and the assessment of weathering. All these require the knowledge and experience of the engineering geologist, whose skills are not commonly known. Promotion, assisted in the media by exposure of global hazards has drawn attention to the discipline and practices.Research on the physical and mechanical stone properties has at last been taken up by major intergovernmental organisations. Large budgets are devoted to take stone testing out of century old routine."High tech" facilities are now applied to make stone-related evaluations more objective and independent of the human factor. Acceptance criteria of testing results require rationalisation. Geotechnical knowledge is important to keep test results within economic restraints and timetables. This is of special importance when linking such factors to environmental planning and control of quarrying and subsequent rehabilitation of the workings. In this paper a bird's eye view of the problems related to dimension stones is provided. Some examples of research trends are also given to exhibit the state-of-the-art.